PENGEMBANGAN WISATA PANTAI EKAS BUANA DESA EKAS KECAMATAN JERUWARU KABUPATEN LOMBOK TIMUR - Beri Andrean Jalil; I Made Murdana; I Putu Gede (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
This research discusses the Tourism Development Strategy of Ekas Buana Beach, Jeruwaru District, East Lombok Regency. This research was conducted to answer the formulation of the problem, namely to find out the tourist attraction of Ekas Buana Beach and find out how the strategy of developing Ekas Buana Beach tourism. The writing of this research is presented descriptively to obtain an overview of the attractiveness and tourism development strategy of Ekas Beach. The methods used in data collection are observation, interviews, documentation and literature studies. The results of this study show that Ekas Beach has an extraordinary beach tourist attraction from the side of the beach that stretches out with the exoticness of the sand which is still very beautiful, the hills that rise around the shoreline, the beauty of the underwater, and clear and calm sea water. Ekas Beach has now begun to be managed by the Village Government and Local Communities by utilizing its strengths. The conclusion that can be drawn regarding the development of Ekas Buana Beach tourism is that there are still weaknesses in the development of beach tourism so that a strategy is needed in planning programs to maximize the development of Ekas Beach in increasing tourist visits to Ekas Beach, this will have a good economic impact on the Village Government and the Community.